Popular education and solidarity economy: The training of social entrepreneurs in Dom Pedrito, Rio Grande do Sul - Garcia Stoll, Vitor; Silva Alves, Simone; Colman Espíndola, Quelen; Loreto Laus Veiga, Geise (Guará Journal, 2016)
This work is the result of a project encompassing popular education and the solidarity economy within the University Extension Project "Training of Social Entrepreneurs," affiliated with the Federal University of Pampa – Dom Pedrito Campus – RS. The basic objective was to demonstrate some relevant data, aspects, and characteristics of the Pedrito Municipal Fair. The project's methodological nature was qualitative research, aiming to understand and map the participants of this fair. A data survey was conducted with these workers, the most relevant information being their educational level, with 52% of the vendors having completed up to the fourth grade of elementary school and 80% being women. It was observed that popular education has become a paradigm in the process of organizing solidarity economic enterprises, developing the construction of a simultaneously self-critical and critical analysis, favoring the strengthening of the collective. Education is a political act, therefore, a collective effort, which re-educates all those involved. It encompasses the posture and attitude toward the world and toward humanity, which differs from one another, depending on their cultures and beliefs. To this end, the analysis was based on the foundations of Freire, Saviani, Singer, Zareto, and others.
Keywords: Popular education; Solidarity economy; Adult and youth education